Use of BHK 21-adapted mesogenic Newcastle disease virus for primary vaccination of chicks - KUMANAN, K; VIJAYRANI, K; PARTHIBAN, M; PADMANABAN, V D (The Indian Journal of Animal Sciences, 2013)
The use of BHK21-adapted mesogenic ’Komarov’ strain of Newcastle disease virus for primary vaccination of chicks was studied. The efficacy of the vaccine was assessed by haemagglutination inhibiting antibody litres and challenge experiments. The BHK21-adapted virus was safe and polent for priming the chicks hy oculonasal route. Further studies are in progress.